Jurnal Rasa Syukur sebagai Media untuk Meningkatkan Penerimaan Diri pada Remaja dengan Perilaku Menyakiti Diri - Muthi’ah, Daffa Nabilahtul; Estria, Suci Ratna; Suroso, Jebul; Yulistiani, Mustiah (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Self harm is a behaviour of harming oneself without the intention of suicide, commonly seen in adolescents as a form of emotional release.. Low levels of self acceptance are one of the factors contributing to this increase, as it tends to cause negative emotions. One intervention that can help increase self acceptance is a gratitude journal, which is an activity of writing down positive things to be grateful for every day. This study aims to determine the effect of gratitude journals on increasing self acceptance in adolescents wit self harming behaviour. The research design uses a pre-experimental pretest-posttest one group design with total sampling technique (N=29). The research instruments include the Self Harm Inventory (SHI) and Berger’s Self Acceptance Scale, while data analysis uses the Shapiro-Wilk test and Paired Sample T-Test. The result showed an increase in the average self acceptance score from 95,79 to 98,79, but this was not statistically significant (p=0,172). In conclusion, gratitude journal can increase self acceptance, but it does not show a significant effect, so further research with larger sample size and longer intervention duration ins needed.